Baert, Patrick (2001). La teoría social en el siglo XX - Noguera, José Antonio (Papers. Revista de Sociologia, 2001)
Reseña de la obra de Patrick Baert aparecida en 2001, La teoría social en el siglo XX. Madrid: Alianza. 272 p.